2006
DOI: 10.1007/s10163-005-0141-6
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental contamination from electronic waste recycling at Guiyu, southeast China

Abstract: The disposal, recycling, and part salvaging of discarded electronic devices such as computers, printers, televisions, and toys are now creating a new set of waste problems. This study is aimed at identifying the sources and quantifying the pollution levels generated from electronic waste (e-waste) activities at Guiyu, Guangdong Province, China, and their potential impacts on the environment and human health. The preliminary results indicate that total polycyclic aromatic hydrocarbons (PAHs) in soil obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
124
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(130 citation statements)
references
References 28 publications
(23 reference statements)
3
124
1
2
Order By: Relevance
“…The toxicological endpoints of concern for environmental levels of PBDEs are likely to be thyroid hormone disruption, neuro-developmental deficit, and cancer (Burreau et al, 1997;McDonald, 2002). PBDE pollution has been confirmed from recent studies that have observed PBDEs in a variety of environmental matrices, including water (Xu et al, 2009), soil Yang et al, 2008), sediment (Leung et al, 2006;Wong et al, 2007), air Li et al, 2008), fish ,and human blood Qu et al, 2007;Roosens et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…The toxicological endpoints of concern for environmental levels of PBDEs are likely to be thyroid hormone disruption, neuro-developmental deficit, and cancer (Burreau et al, 1997;McDonald, 2002). PBDE pollution has been confirmed from recent studies that have observed PBDEs in a variety of environmental matrices, including water (Xu et al, 2009), soil Yang et al, 2008), sediment (Leung et al, 2006;Wong et al, 2007), air Li et al, 2008), fish ,and human blood Qu et al, 2007;Roosens et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…Due to the widely application of brominated flame retardants (BFRs) such as polybrominated diphenyl ethers (PBDEs) in these electronic products, uncontrolled dismantling, acid treatment, and open burning of ewaste result in the emission of PBDEs into the ambient environment (Leung et al, 2006;Wong et al, 2007). Therefore, the growth of e-waste recycling industry particularly in the developing countries has drawn much attention as the source of environmental contamination with PBDEs (Betts, 2009;Leung et al, 2006;Ma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The unregulated processing of E-waste usually recovers gold and other valuable metals by applying some simple techniques such as burning, melting, using acid chemical bath, and so on. These activities can cause severe pollution of highly toxic heavy metals (such as Cu, Cd, Pb and Hg) in aquatic and terrestrial ecosystems, and even to the atmosphere (Deng et al, 2006;Leung et al, 2006). Heavy metals are non-biodegradable, thus persisting for long periods in environmental ecosystems.…”
Section: Introductionmentioning
confidence: 99%